The Relationships Of Work/Non Work Factors And Expatriates International Adjustment. - Surienty, Lilis; Ahmad, Zainal Ariffin (2004)
Integrating work/family linkages, the present study examined the spillover of the different antecedents on Malaysian expatriates international adjustrnent. We also examined the effect of expatriates' favourable attitudes towards an assignment location towards expatriates adjustrnent.